2021
DOI: 10.3389/fimmu.2021.705974
|View full text |Cite
|
Sign up to set email alerts
|

Immunopeptidomics-Guided Warehouse Design for Peptide-Based Immunotherapy in Chronic Lymphocytic Leukemia

Abstract: Antigen-specific immunotherapies, in particular peptide vaccines, depend on the recognition of naturally presented antigens derived from mutated and unmutated gene products on human leukocyte antigens, and represent a promising low-side-effect concept for cancer treatment. So far, the broad application of peptide vaccines in cancer patients is hampered by challenges of time- and cost-intensive personalized vaccine design, and the lack of neoepitopes from tumor-specific mutations, especially in low-mutational b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 33 publications
(21 citation statements)
references
References 94 publications
(149 reference statements)
0
20
0
1
Order By: Relevance
“…Jens Bauer 1,2,3 , Natalie Köhler 4,5 , Yacine Maringer 1,2,3 , Philip Bucher 3,6 , Tatjana Bilich 1,2,3 , Melissa Zwick 4,7 , Severin Dicks 7,8 , Annika Nelde 1,2,3 , Marissa Dubbelaar 1,2,3,9 , Jonas Scheid 1,2,9 , Marcel Wacker 1,2,3 , Jonas S. Heitmann 3,10 , Sarah Schroeder 1,2,11 , Jonas Rieth 1,2 , Monika Denk 1,2,12 , Marion Richter 1,2,12 , Reinhild Klein 13 , Irina Bonzheim 14 , Julia Luibrand 14 , Ursula Holzer 6 , Martin Ebinger 6 , Ines B. Brecht 6 , Michael Bitzer 3,12,15 , Article https://doi.org/10.1038/s41467-022-33746-3…”
Section: Reporting Summaryunclassified
See 1 more Smart Citation
“…Jens Bauer 1,2,3 , Natalie Köhler 4,5 , Yacine Maringer 1,2,3 , Philip Bucher 3,6 , Tatjana Bilich 1,2,3 , Melissa Zwick 4,7 , Severin Dicks 7,8 , Annika Nelde 1,2,3 , Marissa Dubbelaar 1,2,3,9 , Jonas Scheid 1,2,9 , Marcel Wacker 1,2,3 , Jonas S. Heitmann 3,10 , Sarah Schroeder 1,2,11 , Jonas Rieth 1,2 , Monika Denk 1,2,12 , Marion Richter 1,2,12 , Reinhild Klein 13 , Irina Bonzheim 14 , Julia Luibrand 14 , Ursula Holzer 6 , Martin Ebinger 6 , Ines B. Brecht 6 , Michael Bitzer 3,12,15 , Article https://doi.org/10.1038/s41467-022-33746-3…”
Section: Reporting Summaryunclassified
“…T cell-based immunotherapies, comprising immune checkpoint inhibitors (ICIs), CAR-T cells, and bispecific T cell engager antibodies achieved a breakthrough in the treatment of malignant disease [1][2][3][4][5] , adoptive T cell transfer and vaccination strategies hold further promise [6][7][8][9][10] . However, these therapies, which rely on the rejection of cancer cells through recognition of tumor antigens and T cellmediated cytotoxicity are still only available and effective in small subsets of cancer patients and single tumor entities.…”
mentioning
confidence: 99%
“…HLA class I-mediated presentation of the selected epitopes was confirmed by immunopeptidomics ( 120 ). Utilizing a warehouse vaccine concept with 14 HLA class I and class II tumor-associated epitopes, iVAC-XS15-CLL01 is currently under clinical investigation for the treatment of chronic lymphocytic leukemia ( 121 ). The GAPVAC-101 trial investigated the combination of a warehouse vaccine and a fully personalized vaccine in glioblastoma patients and showed the induction of both CD8+ and CD4+ T cell responses ( 122 ).…”
Section: Discussionmentioning
confidence: 99%
“…It is noteworthy that Amplivant, the modified Pam3CSK4, can conjugate synthetic long peptides (SLPs) and elicit stronger DC and T cell stimulation in preclinical models compared to Pam3CSK4 ( 63 ). In 2021 the first-in-human phase I clinical trial NCT02821494 showed HPV16 E6 SLP-conjugated Amplivant induced robust HPV16-specific T cell immunity with good safety profile ( 187 ).XS15 is a TLR1/2 agonist, applied as an adjuvant to a multi-peptide vaccine scheme is in currently active phase I trial NCT04688385 ( 256 ).…”
Section: Recent Advances Of Tlr-targeted Tumor Therapiesmentioning
confidence: 99%